A review of the MIS 5e highstand deposits from Santa Maria Island (Azores, NE Atlantic): Palaeobiodiversity, palaeoecology and palaeobiogeography - Avila S. P.; Melo C.; Silva L.; Ramalho R. S.; Quartau R.; Hipolito A.; Cordeiro R.; Rebelo A. C.; Madeira P.; Rovere A.; Hearty P. J.; Henriques D.; et al. (Quaternary Science Reviews, 2015)
The privileged location of Santa Maria Island (Azores archipelago) in the middle of the North Atlantic makes the fossiliferous outcrops on this island of utmost importance to gain a better understanding of how coeval living communities relate to the broader evolutionary and biogeographic history of the Atlantic basin during the late Neogene and the Quaternary. Here we focus on this island's MIS 5e fossil record, offering a comprehensive review on the palaeobiodiversity, palaeoecology and palaeobiogeography of the biota living in the mid North Atlantic during this interglacial. Several studies in oceanic islands stress the huge impact of sea level changes on insular communities. Pleistocene sea-level changes occur during the short-time events known as "Terminations" (associated to glacial/interglacial shifts) as well as with the onset of glaciations (associated to interglacial/glacial shifts). Both are responsible for extinctions and local disappearance of species, bottleneck effects and formation of new species, resulting in community structure changes. This work increases the number of fossil marine taxa reported from the Last Interglacial deposits of Santa Maria to 143 species. All the 19 new records are molluscs (13 gastropods and 6 bivalves), thus increasing the number of fossil molluscs to 136 species. Although thermophilic members of the "Senegalese" tropical fauna were found in these deposits, many of the most emblematic species (e.g., Persististrombus latus (= Strombus bubonius), Cymbula safiana, Harpa doris, Cardita senegalensis, Barbatia plicata, Ctena eburnea or Hyotissa hyotis) are absent, suggesting that they did not reach the Azores. Our results indicate that the main differences between the species composition of the MIS 5e and the present-day shallow-water Azorean communities are probably due to the dropping of sea surface temperature associated with the onset of the last glaciation, which had both direct and indirect effects on species ecology. A group of 21 thermophilic species was directly ...